Resistance of the Petalangan Community in Mantaining of Local Wisdom in “Kemantan Muda Roh Belian” - Dessy Wahyuni (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2019)
people perceive the world, both identity, self-image and life value. For certain communities, the pressure of globalization through massive enlightenment by developed countries carrying globalization has actually marginalized local values that have been upheld so far. Local values that are seen wisely in various life problems are eroded by the pace of globalization, especially for the  Petalangan community in Riau Province. The life of the Petalangan community is increasingly marginalized by the tumultuous process of development. People live wrapped in misery and poverty. As a writer, B.M. Syamsuddin tried to represent the social and cultural life of the Petalangan people in literary works. Through his short story entitled "Kemantan Muda Roh Belian", he criticized the sociocultural conditions and revealed the irregularities that occurred, especially in the lives of the people of Petalangan. Through the hermeneutic approach carried by Richard E. Palmer, the author interprets the socio-cultural criticism delivered by B.M. Syamsuddin in the short story "Belantan Muda Roh Belian". This criticism is shown through the form of resistance of the local community in maintaining local wisdom that they have inherited from generation to generation. By using an interpretive descriptive method, it can be found that the author raises the character of a kemantan (dukun) as a form of resistance in the Petalangan community in maintaining local wisdom. Thus, the presence of kemantan can be said as a resistance of the Petalangan community to strengthen their existence which frees the community from oppression.